Morphosyntactic development in German-speaking individuals with Down syndrome—longitudinal data - Witecy, Bernadette; Wimmer, Eva; Neitzel, Isabel; Penke, Martina (Frontiers in Psychology, 2023)
Introduction The present study provides longitudinal data on the development of receptive and expressive grammar in children and adolescents with Down syndrome and addresses the role of nonverbal cognitive abilities and verbal short-term memory for morphosyntactic development. Method 17 German-speaking individuals with Down syndrome (aged 4;6 to 17;1 years at first testing (T1)) were assessed twice, 4;4 to 6;6 years apart. For a subset of five participants, there was also a third assessment two years after the second. Receptive grammar, nonverbal cognition and verbal short-term memory were tested using standardized measures. For expressive grammar, elicitation tasks were used to assess the production of subject-verb agreement and of wh-questions. Results At group level, the participants showed a significant increase in grammar comprehension from T1 to T2. However, progress diminished with increasing chronological age. Notable growth could not be observed beyond the age of 10 years. With respect to expressive grammatical abilities, progress was limited to those participants who had mastered verbal agreement inflection around age 10 years. Individuals who did not master verbal agreement by late childhood achieved no progress in producing wh-questions, either. There was growth in nonverbal mental age in the majority of participants. Results for verbal short-term memory followed a similar pattern as those for grammar comprehension. Finally, neither nonverbal cognition nor verbal short-term memory were related to changes in receptive or expressive grammar. Discussion The results point to a slowdown in the acquisition of receptive grammar which starts before the teenage years. For expressive grammar, improvement in wh-question production only occurred in individuals with good performance in subject-verb agreement marking, which suggests that the latter might have a trigger function for further grammatical development in German-speaking individuals with Down syndrome. The study provides no indication that nonverbal cognitive abilities or verbal short-term memory performance determined the receptive or expressive development. The results lead to clinical implications for language therapy.